Exploring the effect of library preparation on RNA sequencing experiments - Wang, Lei; Felts, Sara J.; Van Keulen, Virginia P.; Pease, Larry R.; Zhang, Yuji (Genomics (San Diego, Calif.), 2019)
RNA sequencing (RNA-seq) has become the widely preferred choice for surveying the genome-wide transcriptome complexity in many organisms. However, the broad adaptation of this methodology into the clinic still needs further evaluation of potential effect of sample preparation factors on its analytical reliability using patient samples. In this study, we examined the impact of three major sample preparation factors (i.e., cDNA library storage time, the quantity of input RNA, and cryopreservation of cell samples) on sequence biases, gene expression profiles, and enriched biological functions using RNAs isolated from primary B cell and CD4+ cell blood samples of healthy subjects. Our comprehensive comparison results suggested that different cDNA library storage time, quantity of input RNA, and cryopreservation of cell samples did not significantly alter gene transcriptional expression profiles generated by RNA-seq experiments. These findings shed new lights on the potential applications of RNA-seq technique to patient samples in a regular clinical setting.